2016
DOI: 10.14516/fde.2016.014.020.024
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Work Ethic: Croatian Students’ Perspective

Abstract: Abstract:Teachers' work ethic is one of the key factors in school environment and the overall educational process. It is vital for a teacher to possess and promote the highest standards of work ethic as well as to be a role model to the students. A high level of work ethic thus becomes conditio sine qua non of the teachers' profession and all other educational professions. The topic of teachers' work ethic is insufficiently researched in the national scientific and research circles, and as such, represents a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Teachers' occupational work ethic should be viewed through a culturally appropriate lens (Turk and Vignjević 2016). In South Korea, recognition of the impact of a teacher's behaviors on each student and the quality of the overall nation's education began over sixty years ago.…”
Section: Codes Of Ethics and Principles For Teachersmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers' occupational work ethic should be viewed through a culturally appropriate lens (Turk and Vignjević 2016). In South Korea, recognition of the impact of a teacher's behaviors on each student and the quality of the overall nation's education began over sixty years ago.…”
Section: Codes Of Ethics and Principles For Teachersmentioning
confidence: 99%
“…Only one study was identified through the literature review. Turk and Vignjević (2016) identified teachers' work ethic attributes perceived by Croatian students (Turk and Vignjević 2016, see Table 5). This study intensively reviewed the relevant literature, but did not validate items they developed and used as an instrument.…”
Section: Work Ethic and Work Ethic Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This will open views and attitudes to people to highly evaluate hard and serious work so that it can erode the work attitude that is not serious. According to Turk and Vignjević (2016), the mechanisms and methods for the improvement of work ethic can and must be clearly meant and recognized. Apart from uttering work ethics guidelines in the documents mentioned above, promoting work ethics in each teaching situation is important.…”
Section: Discussionmentioning
confidence: 99%
“…The work ethic of Sultan Agung Pematangsiantar Middle School teachers can be seen from the dimensions of teacher training, grace, teacher training, teaching is calling, teacher training is actualization, teacher training is worship, teacher training is art, teacher training is honor and teacher training is service. The work ethic in the teaching profession is not just an added value for a student's education but part of a teacher's obligations based on the educational process (Turk and Bojana, 2016). The main objectives of this research study are to analyze: (1) the effect of the quality of work discipline on teacher performance; (2) the effect of the teacher's work ethic on teacher performance; (3) the effect of work discipline and work ethic on teacher performance simultaneously.…”
Section: Sultan Agung Pematangsiantar Private Middlementioning
confidence: 99%